The Influence of Digital Marketing and E-WOM on Purchase Decisions in the Marketplace through Brand Trust in Gen Z Students - Darniati, Darniati; Mustari, Mustari; Tadampali, Andi Caezar To; Ahmad, Muh Ihsan Said; Nurwahida, Nurwahida (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to examine the influence of digital marketing and Electronic Word of Mouth (E-WOM) on consumer purchase decisions in marketplace platforms, with brand trust positioned as a mediating variable.   Research Method: The study adopts a quantitative research approach. The sample consists of 361 Generation Z students enrolled in the Economics Education Study Program (cohorts 2022, 2023, and 2024) at the Faculty of Economics and Business, State University of Makassar, Indonesia. Data were collected using structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess direct and mediating relationships among digital marketing, E-WOM, brand trust, and purchase decisions. Results and Discussion: The results indicate that digital marketing, Electronic Word of Mouth (E-WOM), and brand trust have a positive and significant effect on consumer purchase decisions in marketplace platforms. Moreover, brand trust plays a significant mediating role in the relationships between digital marketing and purchase decisions, as well as between E-WOM and purchase decisions. These findings suggest that effective digital communication and positive online consumer interactions enhance trust, which in turn strengthens consumers’ willingness to make purchasing decisions. Implications: In practice, the findings highlight the importance for marketplace platforms and digital marketers of prioritizing trust-building strategies through credible digital marketing content and managing positive E-WOM. For policymakers and educational institutions, the results provide insights into consumer behavior among Generation Z in digital environments. Theoretically, this study reinforces the role of brand trust as a key mechanism linking digital engagement and purchasing behavior. Future research is recommended to expand the sample to other demographic groups, explore additional mediating or moderating variables, and apply longitudinal designs to capture changes in consumer trust and behavior over time.